2019
DOI: 10.3390/dj7040096
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Changes in Oral Hygiene Habits among Adolescents Receiving Orthodontic Treatment

Abstract: The prevalence of malocclusion and a need for orthodontic treatment is high. Orthodontic appliances increase biofilm accumulation by expanding plaque retention sites. The aim of this study was to investigate the self-reported changes in oral hygiene habits among adolescents receiving orthodontic treatment. A cross-sectional study of 291 patients aged 10–17 years (mean (M) = 12.98; standard deviation (SD) = 2.36) was conducted in the Department of Orthodontics, Lithuanian University of Medical Sciences (LSMU) H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…28,30,33,37 Collectively, the findings showed that the use of interdental tools, such as dental floss and interdental brushes, was significantly higher among the patients under active orthodontic treatment (G2) compared to the control group (G1). Similar findings were described by Petrauskiene et al 24 In contrast, many other studies indicated lower utilization of interdental tools among patients. 28,30,37,42,[44][45][46] During orthodontic treatment, ideal oral hygiene may not be achieved simply by the mechanical removal of dental plaque.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…28,30,33,37 Collectively, the findings showed that the use of interdental tools, such as dental floss and interdental brushes, was significantly higher among the patients under active orthodontic treatment (G2) compared to the control group (G1). Similar findings were described by Petrauskiene et al 24 In contrast, many other studies indicated lower utilization of interdental tools among patients. 28,30,37,42,[44][45][46] During orthodontic treatment, ideal oral hygiene may not be achieved simply by the mechanical removal of dental plaque.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies indicated more frequent visits to dental hygienists by orthodontic patients. 24 , 42 In contrast, Atassi and Awartani reported a low frequency of visits to hygienists among orthodontic patients, though there was no control group in their study. 37 The frequency of dental visits in this study also did not differ significantly between the groups.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations